Causal relationships between immediate pre-impact kinematics and post-impact kinetics during drop landing using a simple three dimensional multibody model. (12th February 2021) - Wakabayashi, Kaito; Ogasawara, Issei; Suzuki, Yasuyuki; Nakata, Ken; Nomura, Taishin
Highlights: Drop landing was modelled by a multibody system to assess a risk of sports injuries. Measured and model-predicted impact ground reaction forces (GRFs) showed agreement. Knee valgus torque was estimated for measured and hypothetical landing kinematics. Landing kinematics generating high impact GRF and valgus torques were identified. Abstract: This study aimed to validate a simple dynamic model of single-leg drop-landing to develop a methodological foundation for investigating mechanistic causes of anterior cruciate ligament (ACL) injury and to explore mechanical associations between knee valgus torque and landing kinematics that are considered clinically as a high-risk landing posture for the injury. A triple-inverted-pendulum model in three-dimensional space, composed of rigid-links of head-arms-trunk (HAT), thigh and shank, was employed. We derived causal relationships that can predict post-impact kinetics, including impact ground reaction forces (GRFs) and corresponding knee joint torques from a given body-kinematics immediately before impact, based on an assumption of a completely inelastic collision between a landing foot (the distal end-point of the shank in the model) and the ground. The concordance correlation coefficient (CCC) analysis revealed that our model can achieve an acceptable agreement between experimentally measured and model-predicted impact GRFs and corresponding knee joint torques. The 95 % one-tailed lower confidence limit of CCC of vertical, mediolateral GRFs and the varus/valgus torque were 0.665 > ρ c, a = 0.643, 0.786 > ρ c, a = 0.758 and 0.531 > ρ c, a = 0.508, respectively, for the least acceptable values ρ c, a . Using this model, effects of three types of hypothetical pre-impact kinematics with modulated (i) medial/lateral leaning HAT angle, (ii) forward/backward HAT tilt-angle, and (iii) knee flexion/extension angle on the impact GRF and corresponding knee joint torque were evaluated. We showed that the smaller knee flexion and the greater HAT leaning toward the landing-limb-side, the larger the knee valgus torque is generated, as a mechanical consequence between the specific pre-impact kinematics and the knee loading associated with the risk of ACL injury. Further exploration of hypothetical kinematics using the model in the future work might contribute to identifying the risky landing kinematics beyond experimental limitations.